Brain-Specific Autoantibodies in the Plasma of Subjects with Autistic Spectrum Disorder - CABANLIT, MARICEL; WILLS, SHARIFIA; GOINES, PAULA; ASHWOOD, PAUL; VAN DE WATER, JUDY (Annals of the New York Academy of Sciences, 2007)
:  Although autism spectrum disorder (ASD) is diagnosed on the basis of behavioral parameters, several studies have reported immune system abnormalities and suggest the possible role of autoimmunity in the pathogenesis of ASD. In this study we sought to assess the incidence of brain‐specific autoantibodies in the plasma of children with autism (AU) compared to age‐matched controls including, siblings without ASD, typically developing (TD) controls, and children with other developmental disabilities, but not autism (DD). Plasma from 172 individuals (AU, n= 63, median age: 43 months; TD controls, n= 63, median age: 48 months; siblings, n= 25, median age: 61 months; and DD controls, n= 21, median age: 38 months) was analyzed by Western blot for the presence of IgG antibodies against protein extracts from specific regions of the human adult brain including the hypothalamus and thalamus. The presence of a ∼ 52 kDa MW band, in the plasma of subjects with AU, was detected with a significantly higher incidence when compared to plasma from TD controls (29% vs. 8%, P= 0.0027 and 30% vs. 11%, P= 0.01, in the thalamus and hypothalamus, respectively). Reactivity to three brain proteins (42–48 kDa MW), in particular in the hypothalamus, were observed with increased incidence in 37% of subjects with AU compared to 13% TD controls (P= 0.004). Multiple brain‐specific autoantibodies are present at significantly higher frequency in children with AU. While the potential role of these autoantibodies in AU is currently unknown, their presence suggests a loss of self‐tolerance to one or more neural antigens during early childhood.